Displacement and stress fields around rock fractures opened by irregular overpressure variations - Kusumoto, Shigekazu; Gudmundsson, Agust (Frontiers in Earth Science, 2014)
Many rock fractures are entirely driven open by fluids such as ground water, geothermal water, gas, oil, and magma. These are a subset of extension fractures (mode I cracks; e.g., dikes, mineral veins and joints) referred to as hydrofractures. Field measurements show that many hydrofractures have great variations in aperture. However, most analytical solutions for fracture displacement and stress fields assume the loading to be either constant or with a linear variation. While these solutions have been widely used, it is clear that a fracture hosted by heterogeneous and anisotropic rock is normally subject to loading that is neither constant nor with a linear variation. Here we present new general solutions for the displacement and stress fields around hydrofractures, modelled as two-dimensional elastic cracks, opened by irregular overpressure variations given by the Fourier cosine series. Each solution has two terms. The first term gives the displacement and stress fields due to the average overpressure acting inside the crack; it is given by the initial term of the Fourier coefficients expressing the overpressure variation. The second term gives the displacement and stress fields caused by the overpressure variation; it is given by general terms of the Fourier coefficients and solved through numerical integration. Our numerical examples show that the crack aperture variation closely reflects the overpressure variation. Also, that the general displacement and stress fields close to the crack follow the overpressure variation but tend to be more uniform far from the crack. The present solutions can be used to estimate the displacement and stress fields around any fluid-driven crack, that is, any hydrofracture, as well as its aperture, provided the variation in overpressure can be described by Fourier series. The solutions add to our understanding of local stresses, displacements, and fluid transport associated with hydrofractures in the crust.